Rodents and other terrestrial small mammals from Kanapoi, north-western Kenya. Issue 140 (March 2020) - Manthi, Fredrick K.; Winkler, Alisa J.
Abstract: Excavations at Kanapoi in north-western Kenya have yielded the most numerically abundant and taxonomically diverse early Pliocene (4.19 Ma) terrestrial small mammal assemblage known from Kenya. A minimum of 15 species are reported, including soricids, sengis, leporids, and rodents: all taxa are referable to extant genera, with the exception of the murine rodent, Saidomys . The majority of the terrestrial small mammals are derived from a bone bed at Nzube's Mandible Site, closely associated with the holotype mandible of Australopithecus anamensis . A smaller number were surface-collected or obtained from screening at several other sites, including the Bat Site. Most small mammals from Nzube's Mandible Site and the Bat Site likely represent prey accumulated as regurgitated pellets from owls, in particular barn owls or giant eagle owls. The small mammal fauna is dominated by the spiny mouse, Acomys : the next most commonly recovered taxa are the multimammate mouse, Mastomys, and the African gerbil, Gerbilliscus . Comparisons of the Kanapoi fauna to other eastern African late Miocene-Pliocene (and one Pleistocene) faunas at the generic level suggest the greatest similarity is to Lemudong'o, Kenya, and Omo B and Aramis, Ethiopia. Further similarities with other localities such as Laetoli, Tanzania, and Hadar, Ethiopia, suggest the existence of a corridor for dispersal along the East African Rift Valley between Ethiopia, Kenya, and Tanzania in the early Pliocene. Further comparisons of the relative abundances of individuals in different families (or subfamilies) emphasize the distinctiveness of the Kanapoi small mammal fauna. The Kanapoi fauna is likely derived from a heterogeneous but relatively arid environment.